Perceived Principal Leadership Style and Job Satisfaction Among Secondary School Teachers: A Case Study - Raman, Vasanta Kumari (1999)
The aim of the study was to determine the principal leadership style of principals that relate to job satisfaction level among teachers in the district of Hulu Langat. Four secondary schools from the district of Hulu Langat were involved in t his study. Respondents consisted of two hundred teachers from the four schools. A modified version of the Leadership Behaviour Description Questionnaire (LBDQ) which was taken from Hemphill and Coons (1957) was used. The questionnaire was divided into three parts. Part one of the questionnaire determined the biodata of the respondents. Part two of the questionnaire dealt with questions relating to leadership style of the principal and part three consisted of questions relating to job satisfaction level of teachers.